2015
DOI: 10.1007/s11892-015-0666-6
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap: Race/Ethnic and Socioeconomic Disparities in Obesity

Abstract: Race/ethnic and socioeconomic status (SES) disparities in obesity are substantial and may widen in the future. We review seven potential mechanisms that recent research has used to explain obesity disparities. Those seven mechanisms fall into three broad groups—health behaviors, biological and developmental factors, and the social environment—which incorporate both proximate and upstream determinants of obesity disparities. Efforts to reduce the prevalence of obesity in the U.S. population and to close race/et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 113 publications
(127 reference statements)
5
99
0
4
Order By: Relevance
“…No studies to date have specifically examined differential use of packaged food and beverage nutrient claims by race/ethnicity in the United States, but some studies have found that non-Hispanic whites are more likely to use nutrition labels (specifically nutrition facts panels) than other race/ethnic groups. 25,26 In the context of established nutritional disparities in diet quality for non-Hispanic blacks in the United States, 2729 the findings presented here suggest the need for additional research into the appeal and efficacy of different claim types and how each type might improve or impair overall diet quality when used by certain shoppers.…”
Section: Discussionmentioning
confidence: 88%
“…No studies to date have specifically examined differential use of packaged food and beverage nutrient claims by race/ethnicity in the United States, but some studies have found that non-Hispanic whites are more likely to use nutrition labels (specifically nutrition facts panels) than other race/ethnic groups. 25,26 In the context of established nutritional disparities in diet quality for non-Hispanic blacks in the United States, 2729 the findings presented here suggest the need for additional research into the appeal and efficacy of different claim types and how each type might improve or impair overall diet quality when used by certain shoppers.…”
Section: Discussionmentioning
confidence: 88%
“…For example, an ecological factor that is widely associated with obesity is socioeconomic status (48). This gives rise to the question of whether the differential cost of the three macronutrients 23 Protein intake (kJ/day) Fat + carbohydrate intake (kJ/day)…”
Section: Energy Balancementioning
confidence: 99%
“…In the United States, recent studies suggest that prevalence of childhood obesity is decreasing, however with a disparity among different race or ethnic and socioeconomical status subgroups of the population (Kamali, Hameed, Shih, & Simon, ; Karnik & Kanekar, ; Krueger & Reither, ). In Europe, escalating childhood obesity rates are considered a major public health problem again with a disparity among countries and socioeconomical statues within populations; higher prevalence is observed in southern countries (Ahrens et al, ; WHO, ).…”
Section: Introductionmentioning
confidence: 99%